Czy dwujęzyczność sprzyja kreatywności? Doniesienie z badań - Heryng, Justyna; Obrębska, Monika (Investigationes Linguisticae, 2019)
The paper discusses links between bilingualism and creativity. It begins with a theoretical introduction and then presents research results based on the Creative Behaviour Questionnaire KANH–I (Popek 2000) in a group of 107 high school students. The obtained data was used to test group differences between attendees of classes learning German bilingually and their peers following standard curriculum, which yielded no significant results. The correlation analysis between bilingualism and the dimensions of creative behaviour according to KANH–I yielded no significant results as well. Finally, possible explanations of the results are discussed, along with the limitations of the present study.